The Analysis of Pure Borrowing Technique in Indonesian Translation of â€œDoes My Head Look Big in Thisâ€ Novel (Language Circle: Journal of Language and Literature, 2019)
The process of translation is beyond finding equivalents in the target language (TL) or conveying the general meaning of the source language (SL). For having an acceptable and understandable rendering, some techniques and strategies should be selected as the basis of translating. In â€šDoes my head look big in thisâ€› novel the translator used some techniques but this study only aimed at analyzing the pure borrowing technique. It is a technique in the translation to take a word directly from the SL into the TL without any adjustment. The data of this study were collected by selecting the pure borrowing words found in all chapter of the novel. The result of the analysis shows that there are 85 pure borrowing words used in this novel. The words consist of 4 word classes namely noun, verb, exclamation, and adjective. The calculation mentions 88 % of the pure borrowing words are nouns, 6 % are adjective, 4 % are verb, and 2 % are exclamation. Applying appropriate techniques such as pure borrowing in translating might be needed in order to make the translation product reliable and acceptable for the reader but the translator must consider some aspects that might be related to the translation works itself